Quantitative evaluation of cement paste carbonation using Raman spectroscopy - Tangwei Mi (Nature Portfolio, 2021)
Abstract Carbonation induced corrosion is one of the major durability issues for reinforced concrete structures. To address this issue, it is essential to understand the underlying mechanism of carbonation by detecting the ingress of the CO2 and carbonation depth quantitatively. This paper demonstrates the potential of Raman spectroscopy, as a powerful technique, to implement quantification analysis of cement paste carbonation. In present work, the correlation between the content of the CO3 2− and the Raman peak intensity was initially established by using several standard specimens premixed with certain amount of CO3 2−. The established correlation was then used to investigate the carbonation of the cement paste in a CO2 diffusion scenario, and the results show a good agreement with that obtained by thermogravimetry measurements. Therefore, the feasibility of the Raman spectroscopy to quantify the carbonation degree of the cement paste can be demonstrated.